2016
DOI: 10.1002/chem.201600272
|View full text |Cite
|
Sign up to set email alerts
|

A Thermo‐ and Mechanoresponsive Cyano‐Substituted Oligo(p‐phenylene vinylene) Derivative with Five Emissive States

Abstract: Multiresponsive materials that display predefined photoluminescence color changes upon exposure to different stimuli are attractive candidates for advanced sensing schemes. Herein, we report a cyano-substituted oligo(p-phenylene vinylene) (cyano-OPV) derivative that forms five different solvent-free solid-state molecular assemblies, luminescence properties of which change upon thermal and mechanical stimulation. Single-crystal X-ray structural analysis suggested that tolyl groups introduced at the termini of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 57 publications
(24 reference statements)
1
44
0
Order By: Relevance
“…Because AIE‐active luminophores tend to form loosely‐packed assemblies, mechanical stimuli induces closed‐packing and/or conformational changes, which alter their photoluminescence properties. Another promising approach is the design of molecular structures in which different types of intermolecular interactions can compete against each other . Adopting this strategy, molecules can form several thermodynamically ( meta )stable assembled states and mechanical stimuli can induce interconversions among these states.…”
Section: Figurementioning
confidence: 99%
“…Because AIE‐active luminophores tend to form loosely‐packed assemblies, mechanical stimuli induces closed‐packing and/or conformational changes, which alter their photoluminescence properties. Another promising approach is the design of molecular structures in which different types of intermolecular interactions can compete against each other . Adopting this strategy, molecules can form several thermodynamically ( meta )stable assembled states and mechanical stimuli can induce interconversions among these states.…”
Section: Figurementioning
confidence: 99%
“…Chi and co‐workers reported one tetraphenylethene derivative with 6‐hydroxylbenzothiazole, whose emission can be tuned among four colors through mechanical stimulus protonation and deprotonation, while the chemical structure is changed upon protonation . Sagara and Weder achieved modulation of one cyano‐substituted oligo( p ‐phenylene vinylene) among five emissive states . However, it is a pity that reversible switching cannot be achieved between some states in the both systems developed by Chi and Sagara.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Sagara and Weder achieved modulation of one cyano-substituted oligo(p-phenylene vinylene) amongf ive emissive states. [15] However,i ti sa pity that reversible switching cannot be achieved between some states in the both systemsd eveloped by Chi and Sagara.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of CSB-5 and optical properties in solution CSB-5 was synthesized by adaptingt he procedure reported for the synthesis of CSB-6 [12] by using 1,5-dibromopentane instead of 1,6-dibromohexane. Scheme 1s hows the synthetic route of CSB-5 through three steps from 4-hydroxybenzylcyanide (1).…”
Section: Resultsmentioning
confidence: 99%
“…[11] Sagara, Weder, andc o-workers have later reported that anoth-er derivative, CSB-6 ( Figure 1), can adopt av ariety of polymorphs, depending upon the crystallization method, and exhibit multicolor emission, depending on its morphology. [12] A comparison with otherb is(cyanostyryl)benzene derivatives led to the conclusion that the 4-methylphenyloxymethylene groups attached to the ends of the bis(cyanostyryl)benzene core are important to controlt he molecular packing in the crystalline state and support the formation of av ariety of polymorphs. It stands to reason that the modificationo fs uch appended groups should allow for the creation of other emitting materials with interesting structures andp roperties.…”
Section: Introductionmentioning
confidence: 99%